Just Transformations - Rodríguez, Iokiñe (Pluto Press, 2023)
The climate crisis is the greatest existential threat humanity faces today. The need for a radical societal transformation in the interests of social justice and ecological sustainability has never been greater. But where can we turn to find systemic alternatives? From India, Turkey and Bolivia, to Venezuela, Canada and Lebanon, Just Transformations looks to local environmental struggles for the answers. With each case study grounded in the social movements and specific politics of the region in question, this volume investigates the role that resistance movements play in bringing about sustainable transformations, the strategies and tools they utilise to overcome barriers, and how academics and grassroots activists can collaborate effectively. The book provides a toolkit for scholar-activists who want to build transformative visions with communities. Interrogating each case study for valuable lessons, the contributors develop a conceptualisation of a just transformation that focuses on the changes that communities themselves are trying to produce.